2019
DOI: 10.1525/luminos.82
|View full text |Cite
|
Sign up to set email alerts
|

The Big Gamble: The Migration of Eritreans to Europe

Abstract: Acknowled gmentsThis work would have not been possible without the help and care of my Eritrean informants, whose real names have been changed to protect their safety. They are the protagonists and the soul of this book. Among them I would like to mention my friends Violetta,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…This finding is consistent with Belloni's (2016Belloni's ( , 2019) examination of secondary refugee movements in Europe triggered by unpalatable conditions in the refugees' first country of arrival. Whereas the refugees would be expected to stay in that country, or to even return to their country of origin, it is shown that the EU's migration policies driven by the intention of the Dublin Regulation to stop the refugees from seeking asylum in second EU countries fail to prevent the refugees from doing so.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with Belloni's (2016Belloni's ( , 2019) examination of secondary refugee movements in Europe triggered by unpalatable conditions in the refugees' first country of arrival. Whereas the refugees would be expected to stay in that country, or to even return to their country of origin, it is shown that the EU's migration policies driven by the intention of the Dublin Regulation to stop the refugees from seeking asylum in second EU countries fail to prevent the refugees from doing so.…”
Section: Discussionsupporting
confidence: 88%
“…This argument arises from the response to the question why Africans from the Horn of Africa seem so determined and attempt to migrate to Europe, despite knowing that barriers and challenges exist to their movement. Belloni (2016Belloni ( , 2019 has investigated Eritrean refugees in Italy and why they try to acquire new refugee status in second EU member countries despite the measures in the Dublin Regulation designed to stop such practices as well as a range of risks inherent to irregular migration. Belloni (2019, p. 1) asks "why gamble resources, time and energy again for an unsure outcome," and uses a theory of gambling to argue that the refugees in Italy engage in a "migration lottery" of continuously attempting to proceed to northern European countries in search of asylum in the hope that it will be granted.…”
Section: Introductionmentioning
confidence: 99%
“…The weight of the sacrifice requested of local citizens became increasingly unbearable after the end of the 1998–2000 border conflict with Ethiopia (and the situation remains practically unchanged today even after the 2018 peace agreement 2 ). The eighteen-month national (civil and military) service, which was meant to enable young Eritreans to become adult citizens, has not fulfilled its promise: younger generations have been stuck for decades working in public employment, mostly as soldiers and teachers with low salaries that do not enable them to help their families and pursue their aspirations (Belloni, 2019a; Hirt and Mohammad, 2018). This became the main reason that hundreds of thousands of Eritreans have fled since 2000.…”
Section: Sacrifice and Land: The Meaning Of Citizenship In Eritreamentioning
confidence: 99%
“…Deserters – who are numerous in the country – and irregular emigrants are excluded. However, even those who comply with national service have a hard time enjoying their rights to land: first, even if they obtain government land, they rarely have the money – or the material – to build; second, if they build it, they cannot be there, as most of them are posted as soldiers or teachers in remote areas away from their homes (Belloni, 2019a).…”
Section: Sacrifice and Land: The Meaning Of Citizenship In Eritreamentioning
confidence: 99%
“…Other studies of risk and migration adopt a gambling analogy, whereby the decision to move is akin to a bet, the outcome of which is seen in terms of luck and the successful conclusion of the journey as "winning the jackpot" (Belloni, 2016). Just as people play the lottery even though the chances of winning are almost zero, the chance-albeit small-of successfully arriving at their destination urges migrants to take the gamble and try their luck, even against high odds of danger and risk (Belloni, 2019).…”
Section: Risk In Migration Studiesmentioning
confidence: 99%